2019
DOI: 10.4269/ajtmh.18-0228
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Water Transport and Storage Containers: Assessing Sustained Use of the PackH2O in Rural Haiti

Abstract: . The PackH 2 O water backpack carrier was developed to provide safe storage and relieve stress of head-loading during water transport with traditional containers such as buckets and jerry cans. We conducted an evaluation to assess both self-reported and observed use over a 6-month period between November 2014 and May 2015. A total of 866 packs were distributed to 618 households in six communities in rural Haiti, and 431 and 441 households were surveyed at midline and end line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…While headloading is almost ubiquitous for girls, boys more commonly reported hand-carrying loads or using carts or bicycles. A study in Haiti tested whether backpacks designed to collect and transport water would reduce the physical impacts of head loading; the researchers found that women were less likely to use this intervention on a sustained basis versus men [ 26 ]. Ferguson found that in a rural agricultural community in Kenya, only 13% of women used collection and transport technologies compared to 58% of men [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…While headloading is almost ubiquitous for girls, boys more commonly reported hand-carrying loads or using carts or bicycles. A study in Haiti tested whether backpacks designed to collect and transport water would reduce the physical impacts of head loading; the researchers found that women were less likely to use this intervention on a sustained basis versus men [ 26 ]. Ferguson found that in a rural agricultural community in Kenya, only 13% of women used collection and transport technologies compared to 58% of men [ 15 ].…”
Section: Resultsmentioning
confidence: 99%